Preparation and in vitro release of total alkaloids from alstonia scholaris leaf-loaded mPEG-PMA microspheres - Nianfeng Jiang; Xiangyu Zheng; Yan Feng; Hongtao Wu; Mingwei Yuan; Yi He; Hongli Li; Minglong Yuan (Materials Research Express, 2021)
The total alkaloids extracted from the leaves of Alstonia scholaris (ASAs) have been reported to reduce fever, remove phlegm, and relieve coughs. However, their drug half-lives are short. Thus, to obtain sustained-release preparations of total alkaloids from ASAs, mandelic acid oxyanhydride (mandelic acid OCA) was synthesized by the reaction of L-mandelic acid (MA) with triphosgene, and subsequent copolymerization with polyethylene glycol monomethyl ether (mPEG) of different molecular weights yielded the corresponding mPEG poly-MA (mPEG-PMA) copolymers. ASAs-loaded microspheres were then prepared using the double emulsion method, and their in vitro release (15 d, 37 °C) and in vitro degradation behaviors were studied. The morphology, size, embedding efficiency, and drug loading efficiency were investigated for the prepared microspheres, and screening was carried out using the mPEG _10K -PMA drug-loaded microspheres to analyze their biological characteristics. Anti-inflammatory experiments using Kunming mice and Sprague Dawley rats showed that the microspheres exhibited good anti-inflammatory properties. Moreover, the ASAs-loaded microspheres exhibited a good biocompatibility, and the hemolysis rate was <5%.